2016
DOI: 10.1111/fwb.12791
|View full text |Cite
|
Sign up to set email alerts
|

The roles of elevation and local environmental factors as drivers of diatom diversity in subarctic streams

Abstract: Summary High latitude and altitude freshwater systems are highly sensitive to the effects of global warming and associated environmental changes. Diatoms are widely used as sentinels of environmental change, yet knowledge of diatom community patterns in high latitude and altitude streams remains limited. The aim of this study was to examine alpha and beta diversity of diatoms in subarctic streams in Finland and Norway, and to determine the importance of local environmental factors and elevation in shaping th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 83 publications
8
47
4
Order By: Relevance
“…Empirically, we showed that the relative magnitude of richness change was orders of magnitude smaller than the actual occurrences of extinctions and immigrations (see Figure ), leading to substantial turnover not only of rare species, but also in identity and relative abundance of dominant species (SER a , see Figure d–f). Thus, major aspects of biodiversity change are not (and cannot be) reflected by changes in species richness—consistent with previous studies showing larger changes in composition than richness across temporal and spatial environmental gradients (Hillebrand, Soininen, & Snoeijs, ; Teittinen, Kallajoki, Meier, Stigzelius, & Soininen, ). In addition, our analyses showed that richness trends in and of themselves do not allow conclusions on the effect of a management practice, be it a negative impact or a positive conservation effort, on biodiversity.…”
Section: Discussionsupporting
confidence: 89%
“…Empirically, we showed that the relative magnitude of richness change was orders of magnitude smaller than the actual occurrences of extinctions and immigrations (see Figure ), leading to substantial turnover not only of rare species, but also in identity and relative abundance of dominant species (SER a , see Figure d–f). Thus, major aspects of biodiversity change are not (and cannot be) reflected by changes in species richness—consistent with previous studies showing larger changes in composition than richness across temporal and spatial environmental gradients (Hillebrand, Soininen, & Snoeijs, ; Teittinen, Kallajoki, Meier, Stigzelius, & Soininen, ). In addition, our analyses showed that richness trends in and of themselves do not allow conclusions on the effect of a management practice, be it a negative impact or a positive conservation effort, on biodiversity.…”
Section: Discussionsupporting
confidence: 89%
“…The significant pattern in summer agreed with the studies reviewed by Soininen et al (2007b) and recent studies in diatoms (Teittinen et al 2016). This finding may be due to the relatively small ranges in the measured environmental variables or the fact that we missed some spatially structured abiotic or biotic factors that may have been influential to the distance decay patterns (Teittinen et al 2016). The lack of consistency in distance decay pattern between spring and summer could be explained by comparing the effects of the environmental and spatial variables on beta diversity (based on abundance and presence-absence data).…”
Section: Variation In Explaining Factors Contribution To Spatial Betasupporting
confidence: 90%
“…However, there is no consensus on the distance decay relationship across organism groups, geographic gradients and environments (Soininen et al 2007b). The significant pattern in summer agreed with the studies reviewed by Soininen et al (2007b) and recent studies in diatoms (Teittinen et al 2016). The non-significant pattern in spring was consistent with the findings of 18 lakes in Canada (Beisner et al 2006) and in the floodplain lakes of Brazil (Nabout et al 2009).…”
Section: Variation In Explaining Factors Contribution To Spatial Betasupporting
confidence: 52%
See 1 more Smart Citation
“…For diatoms (unicellular siliceous algae), all the above‐mentioned ecological drivers have been recognized as key factors in driving community structure (diversity and community composition) across mid‐ and high‐latitude regions of Eurasia and North America (Bennett, Cumming, Ginn, & Smol, ; Bouchard, Gajewski, & Hamilton, ; Passy, ; Potapova & Charles, ; Teittinen, Kallajoki, Meier, Stigzelius, & Soininen, ; Vyverman et al., ). Yet, studies in tropical South America are often restricted to a single geographical region (e.g.…”
Section: Introductionmentioning
confidence: 99%